Radiation Detection and Heavy Metals Measurements in Powdered Blood Sample of Leukemia Patients - Hussein, Zakariya A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
This research examines the measurements of radiation detection and heavy metals in blood samples of leukemia and health groups using CR-39 nuclear track detectors and X-ray fluorescence. The results show that the minimum and maximum values of uranium contents found in leukemia blood samples of male (18 years) and female (55 years) patients, respectively. The concentration of heavy metals (Pb, Cd, and Ni) and radium contents is higher in leukemia blood samples, as compared with their concentration in healthy blood samples.